Nuclear envelope structural defect underlies the main cause of aneuploidy in ovarian carcinogenesis - CAPO-CHICHI, D. CALLINICE (My University, 2016)
Background: The Cancer Atlas project has shown that p53 is the only commonly (96 %) mutated gene found in high-grade serous epithelial ovarian cancer, the major histological subtype. Another general genetic change is extensive aneuploidy caused by chromosomal numerical instability, which is thought to promote malignant transformation. Conventionally, aneuploidy is thought to be the result of mitotic errors and chromosomal nondisjunction during mitosis. Previously, we found that ovarian cancer cells often lost or reduced nuclear lamina proteins lamin A/C, and suppression of lamin A/C in cultured ovarian epithelial cells leads to aneuploidy. Following up, we investigated the mechanisms of lamin A/C-suppression in promoting aneuploidy and synergy with p53 inactivation. Results: We found that suppression of lamin A/C by siRNA in human ovarian surface epithelial cells led to frequent nuclear protrusions and formation of micronuclei. Lamin A/C-suppressed cells also often underwent mitotic failure and furrow regression to form tetraploid cells, which frequently underwent aberrant multiple polar mitosis to form aneuploid cells. In ovarian surface epithelial cells isolated from p53 null mice, transient suppression of lamin A/C produced massive aneuploidy with complex karyotypes, and the cells formed malignant tumors when implanted in mice. Conclusions: Based on the results, we conclude that a nuclear envelope structural defect, such as the loss or reduction of lamin A/C proteins, leads to aneuploidy by both the formation of tetraploid intermediates following mitotic failure, and the reduction of chromosome (s) following nuclear budding and subsequent loss of micronuclei. We suggest that the nuclear envelope defect, rather than chromosomal unequal distribution during cytokinesis, is the main cause of aneuploidy in ovarian cancer development.
Keywords: Aneuploidy; Carcinomas; Lamin A/C; Nuclear envelope; Ovarian cancer; Polyploidy.